Strategi Guru Mengajar Di Era Milenial - Ahmad Daud (LPPM STAI Diniyah Pekanbaru, 2020)
This journal aims to describe teaching strategies that can be used by Millennial teachers. Millennial is a generation born with technology that has developed rapidly, so the way of thinking is different when compared to previous generations, where this generation can be said to be a generation that views technology not as a rare item but as a toy item that they play every day. We as a teacher in teaching must adjust to their learning styles so that the learning objectives that we expect can be carried out well. Learning with Applications and Social Media, Learning Oriented on Creativity Optimizing Learning in Groups, and Implementing a Blended Learning System